Politomic dynamic programming problem for the monotonic functions - Bistrickas, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Б. Бистрицкас. Политомическая задача динамического программирования для монотонных функцийV. Bistrickas. Politominis dinaminio programavimo uždavinys